2016
DOI: 10.1007/s10072-016-2801-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence of multiple sclerosis in Italy in 2015

Abstract: Italy is a high risk area for multiple sclerosis (MS) as confirmed by the numerous prevalence and incidence studies conducted in several regions/districts of the country. Nevertheless, there are no recent published epidemiological data, nor studies about the total prevalence of MS in Italy. Our aim was to update as of 2015 the prevalence rates of MS in different geographical areas using already published epidemiological studies, and to estimate the overall prevalence of the disease in Italy. We made a search i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…A recent study [3] noted how, as of 2015, Italy is a high-risk area for MS (average prevalence 110 per 100,000) with no north-south gradient, showing a trend toward an increased prevalence, in line with similar appraisals of nationwide prevalence in other European countries and in North America. Nonetheless, most of the epidemiological data on which these conclusions have been extrapolated have been collected from the islands and in the Northern part of the country.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…A recent study [3] noted how, as of 2015, Italy is a high-risk area for MS (average prevalence 110 per 100,000) with no north-south gradient, showing a trend toward an increased prevalence, in line with similar appraisals of nationwide prevalence in other European countries and in North America. Nonetheless, most of the epidemiological data on which these conclusions have been extrapolated have been collected from the islands and in the Northern part of the country.…”
Section: Discussionmentioning
confidence: 63%
“…While there are currently no whole European-level estimates, it shall be reported that prevalence estimates in other regions of Europe are generally lower, with the notable exceptions of Southern Italy and Sardinia, Scotia, Northern Ireland, and specific regions of Scandinavia [12]. The Italian prevalence rate reported in [3] is 176 per 100,000 (when excluding Sardinia), which shall be compared with our 147.5 per 100,000 after standardization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations